Volume Assessment of the Effect of Obturators on Facial Form Following Surgery for Head and Neck Cancer Using Stereophotogrammetry. Issue 4 (28th February 2019) - Coward, Trevor J.; Richards, Robin; Fenlon, Michael R.; Scott, Brendan J.
Abstract: Purpose: To determine if stereophotogrammetry could be used to determine the effects of obturators on facial contour in relation to the measurement of facial volumes. Materials and Methods: Stereophotogrammetry images were recorded from 20 subjects with and without their obturators in place. These were converted into a stereolithographic format and overlaid. Registrations were made using the tissues on the normal areas of the face. Difference images were created, enabling surface areas and volumes to be calculated. To assess repeatability of measurement, 2 readings were recorded on each of 2 separate registrations. Data analysis between the sets of readings used correlation coefficients and paired t‐tests. Coefficients of repeatability were also calculated. Results: A comparison of readings for the surface areas showed the method of measurement was repeatable with no significant differences between the 2 repeated readings for registration 1 ( p = 0.977, coefficient of repeatability = 101 mm 2 ), registration 2 ( p = 0.085, coefficient of repeatability = 106 mm 2 ), and the mean of the two readings for registration 1 compared with registration 2 ( p = 0.355, coefficient of repeatability = 103 mm 2 ). Similar results were found for the volume measurements with no significant differences between the repeated readings for registration 1 ( p = 0.862, coefficient of repeatability = 229 mm 3 ), registration 2 ( p = 0.200, coefficient of repeatability = 209 mm 3 ), and the mean of the 2 readings for registration 1 compared with those for registration 2 ( p = 0.131, coefficient of repeatability 339 mm 3 ). There was a statistically significant range of volumes that appeared to have been restored by the obturators ( p < 0.0005). Conclusions: Stereophotogrammetry is reliable in assessing the effects of obturators on facial form. In the sample of subjects, obturators generally appeared to be effective in supporting facial tissues following surgical resections of the maxilla and therefore contribute in some degree to the restoration of facial appearance.